MANAJEMEN MUTU PENDIDIKAN KARAKTER MELALUI STRATEGI HABITUTATION BERBSIS NILAI ISLAM DI MI MA’ARIF WRINGINPUTIH BOROBUDUR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the quality management of character education through habituation strategies based on Islamic values at MI Ma'arif Wringinputih Borobudur. The habituation programs developed by the madrasah, including 7K (Cleanliness, Beauty, Order, Security, Comfort, Family, and Longing), as well as religious activities such as dhuha prayers, tadarus, joint prayers, and time discipline, are the main focus in the formation of students' character. The research uses a qualitative approach of the case study type with data collection techniques in the form of observation, in-depth interviews, and documentation. The data analysis was carried out using the Miles and Huberman model, and reinforced by Pierre Bourdieu's theoretical framework of habitus, domain, and capital. The results of the study show that the habituation strategy is applied consistently and integrated in school culture, thus forming Islamic character habitus such as discipline, responsibility, religiosity, and social concern. The 7K program is an effective means of creating a conducive learning environment while supporting the improvement of the quality of character education. Managerially, the implementation of the program meets the principles of planning, implementation, supervision, and continuous improvement. Thus, the habituation strategy based on Islamic values has proven to contribute significantly to improving the quality of character education at MI Ma'arif Wringinputih Borobudur.